Mesocrystalline Nanoparticles: Multi‐Component Mesocrystalline Nanoparticles with Enhanced Photocatalytic Activity (Small 51/2020). Issue 51 (22nd December 2020) - Ko, Min Jun; Park, Bum Chul; Koo, Thomas Myeongseok; Jeon, Yoo Sang; Kim, Myeong Soo; Kim, Young Keun
Abstract : In article number 2004696, Young Keun Kim and co‐workers present multi‐component mesocrystalline nanoparticles (MMNPs), consisting of magnetite, zinc ferrite, and zinc oxide nanocrystals as a magnetically recoverable photo‐catalyst for efficient wastewater purification system. The MMNPs show not only material‐dependent properties from unit nanocrystals, but also synergetic properties from the unique structure, simultaneously. Consequently, MMNPs offer exceptional improvements in heterogeneous catalysts under sunlight.